KLF5 activates lncRNA DANCR and inhibits cancer cell autophagy accelerating gastric cancer progression - Zhiyi Cheng (Nature Portfolio, 2021)
Abstract Cancer cell autophagy has been associated with the progression of gastric cancer (GC), but involvement of long noncoding RNAs (lncRNAs) remains unclear. Initial bioinformatics analysis has identified abnormally highly expressed KLF5 in GC, as well as the predicted regulatory mechanism associating with lncRNA DANCR, miR-194, and AKT2. The expression of KLF5, DANCR, and AKT2 in GC tissue was upregulated, and the expression of miR-194 was downregulated. We knocked KLF5 down and manipulated the expression of DANCR, miR-194, and AKT2 to characterize their roles in GC cell viability, autophagy, and apoptosis. The mechanistic investigations revealed that KLF5 activated the transcription of DANCR in the promoter region and elevated its expression. DANCR acted as a miR-194 sponge to repress its expression in GC. MiR-194 targeted and inhibited AKT2 expression. Silencing KLF5 augmented GC cell autophagy, apoptosis and impeded its viability through the DANCR/miR-194/AKT2 axis. The tumor-inhibiting properties of KLF5 knockdown were substantiated in vivo. Together, our study uncovered the oncogenic role of KLF5-dependent lncRNA DANCR transcription in GC in vivo and in vitro, which implicates the miR-194/AKT2 axis in tumor growth regulation, and it may be a potential therapeutic target for human GC.